Regulatory Ability of Lactiplantibacillus plantarum on Human Skin Health by Counteracting In Vitro Malassezia furfur Effects - Alessandra Fusco; Brunella Perfetto; Vittoria Savio; Adriana Chiaromonte; Giovanna Torelli; Giovanna Donnarumma; Adone Baroni (Journal of Fungi, 2023)
The skin serves as the first barrier against pathogen attacks, thanks to its multifunctional microbial community. Malassezia furfur is a commensal organism of normal cutaneous microflora but is also a cause of skin diseases. It acts on different cell pattern recognition receptors (TLRs, AhR, NLRP3 inflammasome) leading to cellular damage, barrier impairment, and inflammatory cytokines production. Lactobacillus spp. Is an endogenous inhabitant of healthy skin, and studies have proven its beneficial role in wound healing, skin inflammation, and protection against pathogen infections. The aim of our study is to demonstrate the ability of live Lactiplantibacillus plantarum to interfere with the harmful effects of the yeast on human keratinocytes (HaCat) in vitro. To enable this, the cells were treated with M. furfur, either alone or in the presence of L. plantarum. To study the inflammasome activation, cells require a stimulus triggering inflammation (LPS) before M. furfur infection, with or without L. plantarum. L. plantarum effectively counteracts all the harmful strategies of yeast, reducing the phospholipase activity, accelerating wound repair, restoring barrier integrity, reducing AhR and NLRP3 inflammasome activation, and, consequently, releasing inflammatory cytokines. Although lactobacilli have a long history of use in fermented foods, it can be speculated that they can also have health-promoting activities when topically applied.